Sustainable Polymer Reaction Engineering: Towards Fully Renewable Pressure-Sensitive Adhesives - Gabriel, Vida A. (Université d'Ottawa / University of Ottawa, 2022)
This thesis has as its principal goal the development of sustainable pressure-sensitive adhesives (PSAs). To that end, we examined polymer reaction engineering practices and polymer formulations through the lens of the 12 Principles of Green Chemistry. To begin with, we employed emulsion polymerization as our polymer synthesis method because of its use of water instead of hazardous solvents. We also replaced various petroleum-based components with bio-based alternatives (e.g., starch, cellulose nanocrystals), thereby reducing synthesis hazards, increasing product safety and increasing the amount of sustainably sourced raw materials in the PSA. However, changing the synthetic method as well as key components in the formulation presented significant challenges to maintaining PSA performance. This thesis illustrates the challenging path taken towards developing a fully renewable PSA. PSAs should display a specific balance of adhesion and cohesion. Typically, petroleum-based additives (which are often hazardous/toxic) such as tackifiers, cross-linkers, chain transfer agents and rheology modifiers are added to tailor latex properties to fit the intended application. However, because of their inherently opposing effects, an additive used to increase adhesion will weaken the cohesive forces of the polymer, and vice versa. Cellulose nanocrystals (CNCs) are sustainable nanomaterials that have been shown to be effective to resolve the adhesion/cohesion conundrum. In the first part of this project, we developed a new technique to increase CNC loading in emulsion-based PSA formulations beyond the 1-2% limits previously encountered due to high latex viscosity, colloidal instability, and poor film properties. The higher CNC loadings were shown to continuously improve shear strength but resulted in eventual decreases to tack and peel strength. In the second part of this project, we replaced the sulfated CNCs with carboxylated CNCs (cCNCs), which are produced by a process using a “greener” catalyst (i.e., hydrogen peroxide instead of sulfuric acid). The cCNCs’ carboxylate surface groups interacted strongly with the polymer matrix, ultimately leading to catastrophic coagulation. The interactions between cCNCs and other standard latex components were studied and through the creative manipulation of the emulsion polymerization process, a reproducible method to incorporate the cCNCs in a seeded semi-batch reaction yielded stable, high-quality latexes. In the third part of this project, the effect of the cCNCs on the adhesive properties of the nanocomposite latex films was studied and compared to the effects of the sulfated CNCs. AFM imaging revealed that cCNCs interact with latex particles and each other; thus, omitting ultrasonication at the preparation stage was shown to preserve these interactions and lead to greater property enhancements. In the fourth part of this project, starch nanoparticles (SNPs) were used to displace some of the petroleum-based monomer in the production of core-shell (SNP cores, acrylic shell) latexes. SNPs are renewably sourced, inexpensive, and biodegradable. The challenge of locating the SNPs into the particle cores was overcome by crosslinking the SNPs using a food grade cross-linker (sodium trimetaphosphate) and functionalizing them using a sugar-based monomer (EcoMer™). To tune the PSA properties to rival a range of commercial tapes, a method to incorporate CNCs to the SNP-latexes in situ was developed. In addition, because monomers such as 2-octyl acrylate (2OA), styrene, and acrylic acid can be bio-sourced, they were selected as the acrylic shell monomers to encapsulate the SNPs in the nanocomposite latexes. Due to supply chain challenges, n-octyl acrylate was used as a model monomer for 2OA to produce latexes with ~80% bio-content that rivaled commercial Post-It™ notes, masking tapes, and duct tapes. After addressing the sustainability of the polymerization method and polymer components, we posed the question: what are the effects of using renewably sourced and bio-sourced materials on the end-of-life of the PSAs? Because the infrastructure for biodegradation studies at the lab scale via composting does not exist in Canada (to our knowledge), we designed an in-house aerobic composting set-up consisting of a series of bioreactors and sensors capable of measuring the aerobic biodegradability of our polymers in a simulated composting environment. Although not fully tested, the composting setup was designed, and its construction was begun. Steps to complete the construction and validate its operation are detailed. The path towards sustainability is often long and complex. In this four-year study, the re-design of an adhesive synthesis process using a more sustainable approach, emulsion polymerization, along with an 80% bio-sourced formulation required significant corrective measures. Overcoming the technical challenges required mustering all the polymer reaction engineering tools at our disposal. Despite the time and effort required, achieving a more sustainable process is indeed within our grasp.
Keywords: Emulsion Polymerization; Pressusre-Sensitive Adhesives; Polymer Reaction Engineering; Starch Nanoparticles; Cellulose Nanocrystals; Sustainability; Biodegradation